‘Lame ducks’ in the time of HIV/AIDS? exploring female victimhood in selected HIV/AIDS narratives by Zimbabwean female writers - Tagwirei, Cuthbeth (Taylor & Francis (Routledge), 2016)
This article argues that HIV/AIDS narratives written by Zimbabwean women represent a partial view which positions women at the receiving end of the HIV/AIDS pandemic. Women are portrayed as ‘innocent’ and naïve recipients of a disease which finds its sustenance in the way Zimbabwean institutions such as culture, family and the law condone male sexual victimisation of women. Such a view echoes Maureen Kambarami’s (2006) ‘women-as-lameducks’ thesis. By focusing on two narratives, Tendai Westerhorf’s Unlucky in love (2005) and Nancy Mahachi-Harper’s Echoes in the shadows (2004), the researcher explores the ways in which female victimhood is entrenched in Zimbabwean women’s writings about HIV/AIDS. These narratives limit the sexual options available to women in and out of marriage, and stereotype men as callous agents of the disease. By failing to recognise that both men and women can be the victims as well as the perpetrators of abuse, these narratives perpetuate misconceptions about male and female sexuality on the one hand, and HIV/AIDS on the other. Furthermore, portraying female characters as perpetual victims robs women of individual and group agency. Such representations render identities permanent and project the role of women as destined for immanence.